2017
DOI: 10.1186/s12876-017-0572-2
|View full text |Cite
|
Sign up to set email alerts
|

Telbivudine versus entecavir in patients with undetectable hepatitis B virus DNA: a randomized trial

Abstract: BackgroundTelbivudine has been suggested to induce hepatitis B surface antigen (HBsAg) decline to the similar degree as pegylated interferon. We aimed to investigate whether telbivudine could further decrease HBsAg titer in patients who maintain undetectable serum hepatitis B virus (HBV) DNA after initial entecavir treatment.MethodsIn this open-label trial, patients who had serum HBsAg and HBV DNA levels ≥1,000 IU/mL and <60 IU/mL, respectively, following entecavir (0.5 mg/day) treatment for HBeAg-positive chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…When choosing a specific NA, one should consider the efficacy and safety of the drug. Although the class effects of NAs remain unclear, each NA has a unique side effect profiles [223]. Hence, when the efficacy of one NA is expected to be similar to another NA, one should consider patient co-morbidities and the future risk of drug-related side effects when selecting an NA (Refer to “Management in Special Conditions” chapter).…”
Section: Treatment Strategymentioning
confidence: 99%
“…When choosing a specific NA, one should consider the efficacy and safety of the drug. Although the class effects of NAs remain unclear, each NA has a unique side effect profiles [223]. Hence, when the efficacy of one NA is expected to be similar to another NA, one should consider patient co-morbidities and the future risk of drug-related side effects when selecting an NA (Refer to “Management in Special Conditions” chapter).…”
Section: Treatment Strategymentioning
confidence: 99%
“…The four included studies, which involved 297 patients, reported the rates of HBV DNA relapse. [21,22,26,27] Because the heterogeneity was not significant among these studies (group C: P = .98, I 2 = 0%), the fixed-effect method was applied to calculate the overall effects. The rate of HBV DNA relapse was higher in the combination therapy group than in ETV monotherapy group (OR = 19.57, 95% CI: 4.60–83.37, P < .0001; Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, as stated previously, it was not clear which values Jones et al [45] used in the accompanying EE. In published RCTs, HBsAg loss recorded at 48 weeks for nucleosides rarely reaches 4% or higher [12][13][14][15][16][17]; therefore, numerous studies seem to state loss rates that are particularly high in their models.…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to an under-reporting of FC in clinical trials, observational studies and health economic (HE) models. Most published randomised controlled trials (RCTs) record annual HBsAg loss rates that rarely reach > 4% for nucleoside therapies [12][13][14][15][16][17], and usually around 4-10% for PEG IFN [18][19][20][21] (though 20% [22] and 21% [23] have been seen in some cases, with low sample sizes appearing to have an influence, i.e., two and three patients experiencing HBsAg loss, respectively).…”
Section: Introductionmentioning
confidence: 99%